2017
DOI: 10.3201/eid2311.170077
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Pulmonary Tuberculosis Infections and Risk for Multidrug Resistance, Lima, Peru

Abstract: Because within-host Mycobacterium tuberculosis diversity complicates diagnosis and treatment of tuberculosis (TB), we measured diversity prevalence and associated factors among 3,098 pulmonary TB patients in Lima, Peru. The 161 patients with polyclonal infection were more likely than the 115 with clonal or the 2,822 with simple infections to have multidrug-resistant TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Nathavitharana et al 2017 demonstrated polyclonal TB primarily in drug resistant TB. [48] Our observations of statistically significant association of drug resistance with polyclonality reiterate the same findings. CAS lineage contributed to nearly half of the baseline cultures and more of the subsequently grown cultures.…”
Section: Plos Onesupporting
confidence: 86%
“…Nathavitharana et al 2017 demonstrated polyclonal TB primarily in drug resistant TB. [48] Our observations of statistically significant association of drug resistance with polyclonality reiterate the same findings. CAS lineage contributed to nearly half of the baseline cultures and more of the subsequently grown cultures.…”
Section: Plos Onesupporting
confidence: 86%
“…An implicit assumption of this model is that hosts are colonized by clonal pathogen populations that lack genetic variation due to due to bottlenecks that occur during transmission (7,(12)(13)(14)(15). However, hosts can also be colonized by multiple strains of the same pathogen species, giving rise to polyclonal pathogen populations (16)(17)(18)(19). Polyclonal populations contain both novel genetic variation that is acquired in situ and pre-existing variation that reflects differences between the co-colonizing strains.…”
Section: Main Textmentioning
confidence: 99%
“…In this way, the number of repeats at each VNTR locus can be determined using different DNA sizing techniques for comparing isolates. It was found that 50 studies used VNTR-typing to detect M. tuberculosis MSIs, where 28 studies used it as the sole discriminatory method for this purpose (Allix et al, 2004 ; Shamputa et al, 2004 ; Umubyeyi et al, 2007 ; Fang et al, 2008 ; Hofmann-Thiel et al, 2009 ; Mokrousov et al, 2009 ; Stavrum et al, 2009 ; Dickman et al, 2010 ; Mulenga et al, 2010 ; Cohen et al, 2011 ; Gardy et al, 2011 ; Navarro et al, 2011 , 2015 ; Cerezo et al, 2012 ; Furphy et al, 2012 ; Huyen et al, 2012 ; Hingley-Wilson et al, 2013 ; Muwonge et al, 2013 ; Peng et al, 2013 ; Biffa et al, 2014 ; Chaoui et al, 2014 ; Lamine-Khemiri et al, 2014 ; Zetola et al, 2014 ; Barletta et al, 2015 ; Mei et al, 2015 ; Pang et al, 2015 ; Shin et al, 2015 , 2018 ; Ssengooba et al, 2015 ; Streit et al, 2015 ; Wang et al, 2015 ; Zheng et al, 2015 ; Antusheva et al, 2016 ; Hajimiri et al, 2016 ; Hu et al, 2016 ; Egbe et al, 2017 ; Farmanfarmaei et al, 2017 ; Ghielmetti et al, 2017 ; Kamakoli et al, 2017 , 2019 , 2020a , b ; Khosravi et al, 2017 ; Kontsevaya et al, 2017 ; Nathavitharana et al, 2017 ; Sadegh et al, 2017 ; Silva-Pereira et al, 2019 ; Abascal et al, 2020 ; Baik et al, 2020 ; Sichewo et al, 2020 ). In addition, 24-locus MIRU-VNTR was the most commonly used method for detecting M. tuberculosis MSIs, and nearly all (47/50, 94.0%) of the reports used some form...…”
Section: Resultsmentioning
confidence: 99%
“…It was also our intention to help clarify true MSIs as compared to similar events such as re-infection, relapses, and microevolution. While polyclonal infection may refer to microevolution, some studies have also used the term to describe infections that fit the criteria of an MSI (Adams et al, 2012 ; Fujita et al, 2014 ; Farmanfarmaei et al, 2017 ; Kamakoli et al, 2017 , 2020b ; Nathavitharana et al, 2017 ). Due to this lack of consensus regarding the terminology used in the literature and to be consistent in our study, we have selected definitions to describe the different events ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%